Disain dan Simulasi SPWM Multilevel Inverter Tiga Fasa Lima Belas Level Dengan Sumber Input Simetris Terpisah - effendi; Zakwansyah (J-Innovation, 2021)
Design and simulation Multilevel  inverter three-phase  fifteen-level in this research using modulation technics of sinusoidal pulse width modulation (SPWM) in which input voltage sources that used was arranged as symetrical and separate for each phase by using free DC source in form of battery 12 Volt, 24 Volt, and 48 Volt as well as uses seven MOSFETs for switching in each phase. To produce fifteen levels, it can be done by using a combination method of battery arrangement by activating the MOSFET switching circuit according to the results of the comparison between the reference wave in the form of a three-phase sinusoidal wave and the carrier wave in the form of a free DC source by using SPWM modulation circuits. SPWM modulation circuits15level in this research was constructed by using an Op-Amp as a comparator, AND, NOT and OR gates as well as several other electronic components.The H-Bridge circuits is used to reverse the direction of the electric current so that it can to produce alternating current on the load side which is resistive and arranged in a star connection (Y), by using the PSIM simulation program, the THD value that produced  for each phase was relatively the same at 5.6%.